Comparison of the logistics between the conventional instruments and patient-specific templating in total knee replacement in the low-income setting. Issue 4 (December 2021) - Makram, Abdelrahman M; Makram, Omar Mohamed; Youssef, Michael; Hafez, Mahmoud A
Highlights: Around one million TKR operations are done in the USA per year with an average cost of 40, 000 USD per operation. The conventional technique of TKA uses up to 12 trays of instruments (about 300 pieces), requires washing, delivery to a storage facility, re-washing, decontamination, packing, and storing till the next surgery. PST has shown to be logistically more convenient than conventional instrumentation of TKR as PST uses only one tray of one-time use instruments. The PST appears to be more beneficial in the low-income setting and low-volume hospitals. Abstract: Background: Total knee replacement (TKR) is a complex operation and its conventional instrumentation system has around 300 pieces to perform and more than 50 technical steps. New techniques were introduced, such as patient-specific instrumentation (PSI), robotics, and navigation to facilitate the TKR operation. This study aims to compare the logistics between conventional instrumentation and patient-specific templating (PST) in the low-income setting. Methods: We compared the logistics for the conventional and the PST techniques while performing TKR. The comparison included the number of instruments and trays, equipment delivery, packaging, sterilization, intraoperative setup, and post-operative handling. Results: The surgical trays to complete one conventional TKR were 6–12 trays while for the PST, only one tray was needed. Conventional instruments can reach the hospital in 24 h while the delivery time of the PST may take from 3 to 5 days. The time needed to sterilize the conventional could be done overnight in the small hospitals as compared to a few hours in PST. In addition, PST has no special postoperative steps, unlike the conventional, which requires washing, delivery to a storage facility, re-washing, decontamination, packing, and storing till the next surgery. Conclusion: The logistics for conventional instruments are more complex. Although there was no cost-effectiveness analysis, it has been observed that the PST technique has a positive effect on rationalizing resources by consuming less time in the central sterilization unit and reducing the operating time.